Design, Preparation and Characterization of Polystyrene Nanospheres Based-Porous Structure towards UV-Vis and Infrared Light Absorption - Jujur Wibawa, Pratama (Elsevier, 2011)
Porous Polystyrene nanospheres (PSNs)-Cd metal thin film of about 375.72 angstrom (Ǻ) on hydrophilic silicon wafer has been successfully fabricated from its liquid colloidal prepared by 40 KHz ultrasound for 45 minute at room temperature. This porous fabrication was aiming to confirm the proposed structure of PSNs based-porous thin film models depicted in Fig.1. Surface morphology of the porous thin film explored with a field emission scanning electron microscopy (FESEM) showed that Cd metals atomic particles might be deposited on the PSNs particles surface so that they could enhance the porosity of the thin film material. Absorption capability of the porous thin film assayed using both ultraviolet-visible (UV-Vis) and infrared (IR) light proved that Cd metals atomic particles were a main part of the porous thin film which could enhance significantly the absorption performance. It could be concluded that both kind of nano- sunken and nano-wells unique binding sites might have been generated inside the pores during fabricating them.